P064: Effect of increased availability of pre-authorized radiological test ordering on CT scan utilization in the emergency department. (2nd June 2016) - Huszarik, K.; Wood, K.; Columbus, M.; Dukelow, A.
Abstract : Introduction: Computed tomography (CT) scan utilization has increased dramatically over the past 25 years. This has sparked concern for potential overuse leading to unnecessary radiation exposure for patients and increased health care costs, without any improvement in health outcomes. In order to improve workflow through the Emergency Department (ED) at our institution, an existing pre-authorization policy during weekday business hours allows emergency physicians to order CT scans directly without the need for approval from a radiologist. This policy was recently expanded on September 28, 2015 to allow pre-authorized CT scan orders during weekday evening hours. The objective of our study is to evaluate the impact of increased availability of pre-authorized CT scan ordering on CT scan utilization and patient flow through the ED at two tertiary care hospitals in London, Ontario.Methods: This is a retrospective review comparing monthly CT scan utilization rates in the pre-implementation period from September 28, 2014 to February 28, 2015, to rates in the post-implementation period from September 28, 2015 to February 28, 2016. Length of stay parameters including time from physician initial assessment to CT scan order, completion, report and patient discharge will also be compared between the groups.Results: Results will be presented at CAEP 2016. No significant difference is expected in the monthly number of CT scans ordered per registered ED visits between the pre- and post-implementation groups. We also anticipate a significantly shorter average length of stay for patients receiving a CT scan in the post-implementation group.Conclusion: We expect there will be no significant increase in CT scan utilization with increased availability of pre-authorized CT scan ordering in our EDs. We also anticipated decreased patient length of stay leading to improved patient flow through the ED. Findings may offer support for organizations to safely implement or increase availability of pre-authorized CT scan orders to help improve patient flow and decrease costs in the ED.